2022
DOI: 10.3390/ijms23020878
|View full text |Cite
|
Sign up to set email alerts
|

High-Accuracy Relative Biological Effectiveness Values Following Low-Dose Thermal Neutron Exposures Support Bimodal Quality Factor Response with Neutron Energy

Abstract: Theoretical evaluations indicate the radiation weighting factor for thermal neutrons differs from the current International Commission on Radiological Protection (ICRP) recommended value of 2.5, which has radiation protection implications for high-energy radiotherapy, inside spacecraft, on the lunar or Martian surface, and in nuclear reactor workplaces. We examined the relative biological effectiveness (RBE) of DNA damage generated by thermal neutrons compared to gamma radiation. Whole blood was irradiated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…The approach behind our RBE model explicitly considers the specific geometry of the target and the change in the neutron-induced charged particle field, both with target size and with penetration in a large-size target. Of interest, other models 33,34 indicate an increase of quality factors below 10 −3 MeV, and in vitro experimental studies 35 have reported high RBE for DNA damage (dicentric chromosome assay and cytokinesis-block micronucleus assay) for thermal neutrons. It has to be recalled however that such increase is particularly manifested only considering a small target size, as thermal neutron dose to a large size receptor is always largely dominated by the photon component, hence leading to an overall low effectiveness in inducing damage.…”
Section: Discussionmentioning
confidence: 99%
“…The approach behind our RBE model explicitly considers the specific geometry of the target and the change in the neutron-induced charged particle field, both with target size and with penetration in a large-size target. Of interest, other models 33,34 indicate an increase of quality factors below 10 −3 MeV, and in vitro experimental studies 35 have reported high RBE for DNA damage (dicentric chromosome assay and cytokinesis-block micronucleus assay) for thermal neutrons. It has to be recalled however that such increase is particularly manifested only considering a small target size, as thermal neutron dose to a large size receptor is always largely dominated by the photon component, hence leading to an overall low effectiveness in inducing damage.…”
Section: Discussionmentioning
confidence: 99%
“…The Lunar Neutron Probe Measurements conducted during the Apollo 17 showed a significant increase in the flux of thermal and epithermal neutrons up to 1 m below the Lunar surface (Woolum, 1975). Recent high accuracy measurements have indicated that the relative biological effectiveness (RBE) values for thermal neutrons can be 4 times higher than the previous recommended value of 2.5 (Paterson, 2022). Given their high RBE values the thermal neutron component should be considered for radiation shielding countermeasures.…”
Section: Introductionmentioning
confidence: 99%